Spending on Public Infrastructure : A Practitioner's Guide - Briceno-Garmendia, Cecilia; Sarkodie, Afua (2012)
This paper provides a methodological tool to support the collection and preparation of standardized, comprehensive data regarding public spending on infrastructure services that can be rigorously compared across countries. Infrastructure is defined to cover six sectors: irrigation, energy (primarily power), transport, communication, wastewater management, and water supply. The guide is designed to provide a much richer and more complete measurement of infrastructure spending than the limited highly aggregated data currently available through the IMF Government Financial Statistics. Originally developed for Africa, the methodology is relevant and readily applicable to any developing country. With the aim of being as comprehensive as possible, the methodology covers central and sub-national government expenditures, non-budgetary vehicles (such as road funds), state-owned enterprises (SOEs), and public-private partnerships (PPPs). While the methodology focuses on collecting quantitative data on the level and composition of spending, this is complemented with qualitative data that provides the institutional context. Importantly, the methodology allows for cross-classification of infrastructure spending by purpose (power, roads, etc) and by function (operational versus capital spending). This guide provides practical guidance -- including concepts, definitions, and classifications -- for each of the three stages of work, namely: (i) pre-field, (ii) field, and (iii) back office.